The Influence of Artificial Intelligence (AI) and Information Communications Technology (ICT) on Employee Mental Health With Technostress as Mediation in Generation Z Employees in West Kalimantan - Doni Bagaskara; Hasanudin Hasanudin; Karsim Karsim; Maria Christiana Iman Kalis; Ilzar Daud Iman Kalis (Komunitas Dosen Indonesia, 2024)
This study investigates the influence of artificial intelligence (AI) and information system quality (ICT) on the mental health of Generation Z employees in West Kalimantan, with a specific focus on technostress as a mediating factor. The research uses an explanatory quantitative approach, employing a partial least squares-based structural equation model (PLS-SEM) via SmartPLS 4 software. The sample consists of 200 Generation Z employees, selected through purposive sampling based on age (18-27 years) and experience using AI and ICT for at least one year. The study reveals that AI positively and significantly affects employee mental health, while ICT has a negative and insignificant impact on employee mental health. Furthermore, technostress positively and significantly mediates the relationship between AI, ICT, and mental health. This research provides evidence that the effective use of AI and ICT, combined with proper technostress management, can enhance employee well-being and productivity, fostering innovation and efficiency in West Kalimantan’s workforce, ultimately positioning the region to leverage Generation Z’s digital skills to drive economic growth and attract investment in emerging tech sectors.